MicroRNA-221/222 Family Counteracts Myocardial Fibrosis in Pressure Overload–Induced Heart Failure. Issue 2 (February 2018) - Verjans, Robin; Peters, Tim; Beaumont, Francisco Javier; van Leeuwen, Rick; van Herwaarden, Tessa; Verhesen, Wouter; Munts, Chantal; Bijnen, Mitchell; Henkens, Michiel; Diez, Javier; de Windt, Leon J.; van Nieuwenhoven, Frans A.; et al.
Abstract : Pressure overload causes cardiac fibroblast activation and transdifferentiation, leading to increased interstitial fibrosis formation and subsequently myocardial stiffness, diastolic and systolic dysfunction, and eventually heart failure. A better understanding of the molecular mechanisms underlying pressure overload–induced cardiac remodeling and fibrosis will have implications for heart failure treatment strategies. The microRNA (miRNA)-221/222 family, consisting of miR-221-3p and miR-222-3p, is differentially regulated in mouse and human cardiac pathology and inversely associated with kidney and liver fibrosis. We investigated the role of this miRNA family during pressure overload–induced cardiac remodeling. In myocardial biopsies of patients with severe fibrosis and dilated cardiomyopathy or aortic stenosis, we found significantly lower miRNA-221/222 levels as compared to matched patients with nonsevere fibrosis. In addition, miRNA-221/222 levels in aortic stenosis patients correlated negatively with the extent of myocardial fibrosis and with left ventricular stiffness. Inhibition of both miRNAs during AngII (angiotensin II)–mediated pressure overload in mice led to increased fibrosis and aggravated left ventricular dilation and dysfunction. In rat cardiac fibroblasts, inhibition of miRNA-221/222 derepressed TGF-β (transforming growth factor-β)–mediated profibrotic SMAD2 (mothers against decapentaplegic homolog 2) signaling and downstream gene expression, whereas overexpression of both miRNAs blunted TGF-β–induced profibrotic signaling. We found that the miRNA-221/222 family may target several genes involved in TGF-β signaling, including JNK1 (c-Jun N-terminal kinase 1), TGF-β receptor 1 and TGF-β receptor 2, and ETS-1 (ETS proto-oncogene 1). Our findings show that heart failure–associated downregulation of the miRNA-221/222 family enables profibrotic signaling in the pressure-overloaded heart. Abstract : Supplemental Digital Content is available in the text.